The efficacy of resistance training in hypoxia to enhance strength and muscle growth: A systematic review and meta-analysis - Ramos-Campo, D. J.; Scott, B. R.; Alcaraz, P. E.; Rubio-Arias, J. A. (European Journal of Sport Science, 2018)
Recent studies have reported that resistance training in hypoxia (RTH) may augment muscle size and strength development. However, consensus on the effects of RTH via systematic review and meta-analysis is not yet available. This work aimed to systematically review studies which have investigated using RTH versus normoxic resistance training (NRT) to improve muscular size and strength, and to perform a meta-analysis to determine the effect of RTH on these adaptive parameters. Searches were conducted in PubMed, Web of Science and the Cochrane Library from database inception until 17 June 2017 for original articles assessing the effects of RTH on muscle size and strength versus NRT. The effects on outcomes were expressed as standardized mean differences (SMD). Nine studies (158 participants) reported on the effects of RTH versus NRT for muscle cross-sectional area (CSA) (n = 4) or strength (n = 6). RTH significantly increased CSA (SMD = 0.70, 95% confidence intervals (CI) 0.05, 1.35; p = .04) and strength (SMD = 1.88; 95% CI = 1.20, 2.56; p < .00001). However, RTH did not produce significant change in CSA (SMD = 0.24, 95% CI -0.19, 0.68, p = .27) or strength (SMD = 0.20; 95% CI = -0.27, 0.78; p = .23) when compared to NRT. Although RTH improved muscle size and strength, this protocol did not provide significant benefit over resistance training in normoxia. Nevertheless, this paper identified marked differences in methodologies for implementing RTH, and future research using standardized protocols is therefore warranted.